2022
DOI: 10.1186/s12974-022-02547-2
|View full text |Cite
|
Sign up to set email alerts
|

Spotlight on pyroptosis: role in pathogenesis and therapeutic potential of ocular diseases

Abstract: Pyroptosis is a programmed cell death characterized by swift plasma membrane disruption and subsequent release of cellular contents and pro-inflammatory mediators (cytokines), including IL‐1β and IL‐18. It differs from other types of programmed cell death such as apoptosis, autophagy, necroptosis, ferroptosis, and NETosis in terms of its morphology and mechanism. As a recently discovered form of cell death, pyroptosis has been demonstrated to be involved in the progression of multiple diseases. Recent studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 280 publications
(398 reference statements)
0
18
0
Order By: Relevance
“…The increasing incidence of diabetes and an aging society require further research into the pathogenesis and potential targets of cataract therapy. Recent reports on the involvement of pyroptosis in eye diseases seem promising, including cataracts extensively discussed by Chen et al [ 131 ], describing pyroptosis as an inflammatory form of cell death executed by gasdermins, a family of transmembrane pore-forming proteins activated via inflammasome-dependent or inflammasome-independent pathways. During the exploration of different types of cell death, they found that the relationship between cell death forms is complicated, and a myriad of ties between pyroptosis and other cell death in ocular diseases remain to be discovered.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…The increasing incidence of diabetes and an aging society require further research into the pathogenesis and potential targets of cataract therapy. Recent reports on the involvement of pyroptosis in eye diseases seem promising, including cataracts extensively discussed by Chen et al [ 131 ], describing pyroptosis as an inflammatory form of cell death executed by gasdermins, a family of transmembrane pore-forming proteins activated via inflammasome-dependent or inflammasome-independent pathways. During the exploration of different types of cell death, they found that the relationship between cell death forms is complicated, and a myriad of ties between pyroptosis and other cell death in ocular diseases remain to be discovered.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…Low-density lipoprotein (LDL) is another important component of drusen. Increased plasma levels of oxidized low-density lipoprotein (ox-LDL) were demonstrated in AMD patients, and were directly related to increased expressions NLRP3, caspase-1 and IL-1β in ARPE-19 cells, leading to pyroptosis-mediated RPE cell death [ 43 ]. LDL is readily oxidized to generate ox-LDL, which is absorbed by RPE, thus increasing ROS levels and oxidative stress.…”
Section: Pyroptosis and Degenerative Diseases Of The Elderlymentioning
confidence: 99%
“…Granzyme A from cytotoxic lymphocytes cleaves GSDMB, and granzyme B from natural killer cells and cytotoxic T lymphocytes cleaves GSDME to induce tumor cell pyroptosis [40][41][42]. Neutrophil elastase and cathepsin G can directly cleave GSDMD to activate pyroptosis [43]. Streptococcus pyogenes expresses a cysteine protease SpeB virulence factor that triggers pyroptosis by cleaving GSDMA after Gln246 [44,45].…”
Section: Pyroptosis Pathwaysmentioning
confidence: 99%
“…Drusen formation activates the NACHT, LRR and PYD domain-containing protein 3 (NLRP3) inflammasome via the complement C1q (C1Q), a component of drusen [ 27 ]. NLRP3 is one of the central molecules involved in pyroptosis, a programmed cell death characterized by swift plasma membrane disruption and the subsequent release of cellular content, including typical pro-inflammatory mediators such us IL-1β and IL-18 [ 28 ]. Furthermore, changes in the extracellular matrix (ECM) affecting collagen layer structure and elasticity can promote the loss of differentiation and the epithelial mesenchymal transition (EMT) of healthy RPE cells [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%